Pengaruh Interaksi Sosial, Kepercayaan, Terhadap Niat Beli Konsumen Perempuan Dalam E-Commerce Di Kota Makassar - Ayesha, Shakira; Kumalasari Yo, Sacca; Monalisa, Monalisa (Jurnal Online Manajemen ELPEI, 2025)
The rapid growth of e-commerce in Indonesia, particularly among female consumers in Makassar, highlights the increasing importance of understanding the factors influencing online purchasing behavior. This study aims to examine the impact of social interaction and trust on female consumers' purchase intentions in Makassar’s e-commerce landscape.A quantitative research approach was applied using a survey method to collect data from active online shoppers in Makassar. The sampling technique employed was purposive sampling, and data was gathered through structured questionnaires utilizing a five-point Likert scale. The data analysis involved validity and reliability tests, R-square analysis, and path coefficient analysis to evaluate the relationships between social interaction, trust, and purchase intention.The results revealed that social interaction significantly influences trust (t-statistic = 6.747, p-value = 0.000) and purchase intention (t-statistic = 3.874, p-value = 0.000). Additionally, trust positively impacts purchase intention (t-statistic = 4.021, p-value = 0.000). These findings underscore the crucial role of social engagement in shaping consumer confidence in e-commerce platforms, where trust acts as a mediator in online purchasing decisions. The study also emphasises the importance of transparency, user-generated reviews, and influencer marketing in fostering consumer trust and encouraging online purchases.These insights have significant implications for e-commerce businesses, highlighting the need to develop interactive marketing strategies, enhance trust-building mechanisms, and improve consumer engagement. Future research could explore additional factors, such as algorithmic recommendations, micro-influencer effects, and interactive features in e-commerce platforms.Keywords: Social interaction, trust, purchase intention, e-commerce, female consumers.